2023
DOI: 10.1037/int0000274
|View full text |Cite
|
Sign up to set email alerts
|

A randomized trial of group therapy for resource activation for patients with affective disorder.

Abstract: Resource activation is a common factor of psychotherapy and has an effect on the treatment success regardless of the specific orientation. A balanced focus on resources and problems seems to constitute a promising therapy method. Therefore, the aim of this study was to evaluate the effects of a novel group therapy for resource activation (GTRA) for inpatients with unipolar depressive and bipolar affective disorders experiencing a depressive episode. Primary outcome criteria were the change in resources and in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 87 publications
0
3
0
Order By: Relevance
“…Digital health is a promising approach to increase the utilisation and quality of prevention interventions by using information and communication technologies to meet health-related needs 21. Studies have shown that psychosocial aspects can be strengthened during inpatient treatment with the application of various therapies or elements such as individual or group training or psychoeducation 22–24. In addition, positive outcomes have been demonstrated for digitally supported mental health prevention interventions using a variety of therapeutic or psychoeducational elements 25–27.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Digital health is a promising approach to increase the utilisation and quality of prevention interventions by using information and communication technologies to meet health-related needs 21. Studies have shown that psychosocial aspects can be strengthened during inpatient treatment with the application of various therapies or elements such as individual or group training or psychoeducation 22–24. In addition, positive outcomes have been demonstrated for digitally supported mental health prevention interventions using a variety of therapeutic or psychoeducational elements 25–27.…”
Section: Introductionmentioning
confidence: 99%
“…21 Studies have shown that psychosocial aspects can be strengthened during inpatient treatment with the application of various therapies or elements such as individual or group training or psychoeducation. [22][23][24] In addition, positive outcomes have been demonstrated for digitally supported mental health prevention interventions using a variety of therapeutic or psychoeducational elements. [25][26][27] Among the digitally supported prevention interventions that were not exclusively related to work, various outcomes were examined in employees, such as work stress, 25 perceived stress, 26 anxiety and quality of life, 27 which are either related to or exacerbated by the work environment.…”
mentioning
confidence: 99%
“…Resource activation is used, among other things, in positive psychotherapy and strength-based approaches, involving the activation of positive emotions, character strengths, positive relationships and intrinsically motivated accomplishments ( Rashid, 2015 ). Grawe (1997) describes resource activation as an unspecific cross-therapeutic mechanism of action in psychotherapy and its positive effects have been demonstrated in numerous studies (e.g., Goldbach et al, 2023 ). In the literature, resources are frequently divided into personal/individual (internal) and social (external) resources (e.g., Martin, 2002 ; Holmgreen et al, 2017 ; Salgado et al, 2022 ; Siegwart et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%